Bibliography of Index Numbers : an international team project - Maunder, W. F. (London : The Athlone Press, 1970)
This work is a revised and greatly enlarged edition of a small book distributed by the international statistical institute in 1956. This edition includes a chronological index up to the end of 1967.
Includes index
usc 29/10/2021
Ref.
Keywords: Index numbers (Economics)